The effect of a silica support: a density functional theory study of the C–H bond activation of ethane on a nickel oxide cluster. (29th October 2015) - Lin, Xufeng; Xi, Yanyan; Phillips, David L.; Guo, Wenyue
Abstract : The support effect is an important issue in heterogeneouscatalysis . A systematic density functional theory computational study is reported here to better understand theC–H bond activation steps in the reaction between C2 H6 and a model silica‐supported Ni3 O3 cluster, as well as that between C2 H6 and an unsupported Ni3 O3 cluster. Two mechanisms, namely, a radical mechanism (denoted as mechanism A ) and a concerted mechanism (denoted as mechanism B ) were examined. Both of these mechanisms contain two steps. For theC–H bond activation taking place via mechanism A, the involvement of the model silica support does not change the most favorable pathway significantly; however, it does result in a modest increase in the reaction barrier and the overall Gibbs energy change. For theC–H bond activation taking place via mechanism B, the involvement of the model silica support leads to an increase in the reaction barrier in the first step. The product of this step has a noticeable difference in the structures for the Ni3 O3 moiety in the unsupported and model silica‐supported systems. The result of charge analysis shows that there is no noticeablecharge transfer between the silica support and Ni3 O3 when they are in the starting reactants, while there is an electron withdrawal from Ni3 O3 by the silica support when they are in transition states, intermediates, or products. The results here provide deeper insights into the support effect on theC–H bond activation of lower alkanes on supported transition metal catalysts. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : New insights into the support effect of silica on the C–H bond activation of ethane when reacting with a nickel oxide cluster are provided with density functional theory calculation. The changes in the reaction barrier via different mechanisms are associable with the charge transfer between the support and the reactants.